Dandy-Walker variant with precocious puberty: a rare association. Issue 1 (28th November 2018) - Rajput, Rajesh; Mishra, Sanat; Ahlawat, Parul; Yadav, Pawan Kumar
Abstract : Precocious puberty is characterised by premature appearance of secondary sexual characteristics before the age of 7 years in girls and 9 years in boys. Dandy-Walker malformation comprises a spectrum of intracranial malformations of the posterior fossa. We present a case of a 7-year-old male child who has presented with features of central precocious puberty and on further evaluation has been found to have Dandy-Walker variant and secondary hypothyroidism. The following case report describes this association which is extremely rare and has never been described in literature.